2007
DOI: 10.2202/1935-1682.1618
|View full text |Cite
|
Sign up to set email alerts
|

The Short and Long Run Effects of Daylight Saving Time on Fatal Automobile Crashes

Abstract: Prior literature suggests that Daylight Saving Time (DST) can both increase the risk of automobile crashes in the short run and decrease the risk of automobile crashes in the long run. We use 28 years (1976-2003) of automobile crash data from the United States, and exploit a natural experiment arising from a 1986 federal law that changed the time when states switched to DST to identify the short run and long run effects of DST on automobile crashes. Our findings suggest that (1) DST has no significant detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
1
25
3
Order By: Relevance
“…Notably, many previous studies have found a net reduction in crashes due to the ambient light mechanism (Ferguson et al 1995;Broughton, Hazelton, and Stone 1999;Coate and Markowitz 2004;and Sood and Ghosh 2007), something I do not find evidence of during the 2002-2011 sample period. Further, existing studies reach contradictory conclusions about whether sleep deprivation increases crash risk-something I find strong evidence of.…”
Section: Evidence From Earlier Yearscontrasting
confidence: 69%
See 4 more Smart Citations
“…Notably, many previous studies have found a net reduction in crashes due to the ambient light mechanism (Ferguson et al 1995;Broughton, Hazelton, and Stone 1999;Coate and Markowitz 2004;and Sood and Ghosh 2007), something I do not find evidence of during the 2002-2011 sample period. Further, existing studies reach contradictory conclusions about whether sleep deprivation increases crash risk-something I find strong evidence of.…”
Section: Evidence From Earlier Yearscontrasting
confidence: 69%
“…39 Coren (1996) and Varughese and Allen (2001) find an increase in crashes on the Monday following the spring transition into DST, while Vincent (1998), Sood and Ghosh (2007), and Lahti et al (2010) suggest no effect. 40 To remain consistent with Sood and Ghosh (2007), I omit the first year of FARS data (1975) because it was subject to alternative DST cutoffs following the 1973 oil crisis.…”
mentioning
confidence: 99%
See 3 more Smart Citations